2017
DOI: 10.1371/journal.pone.0176070
|View full text |Cite
|
Sign up to set email alerts
|

Metallothioneins regulate the adipogenic differentiation of 3T3-L1 cells via the insulin signaling pathway

Abstract: Knockout of metallothionein (MT) genes contributes to a heavier body weight in early life and the potential to become obese through the intake of a high fat diet (HFD) in mice. It has thus been suggested that MT genes regulate the formation of adipose tissue, which would become the base for later HFD-induced obesity. We evaluated the fat pads of mice during the lactation stage. The fat mass and adipocyte size of MT1 and MT2 knockout mice were greater than those of wild type mice. Next, we assayed the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
(55 reference statements)
2
7
0
Order By: Relevance
“…Other authors that have used NAC during adipocyte differentiation, reported similar results [18,20,38,39]. Therefore, we could speculate about a possible use of this molecule as a new drug or as an adjuvant to decrease lipid content in human adipose tissue during obesity development.…”
Section: Discussionsupporting
confidence: 74%
“…Other authors that have used NAC during adipocyte differentiation, reported similar results [18,20,38,39]. Therefore, we could speculate about a possible use of this molecule as a new drug or as an adjuvant to decrease lipid content in human adipose tissue during obesity development.…”
Section: Discussionsupporting
confidence: 74%
“…In our observations, co-administration of NAC resulted in a remarkable reduction of nal body weight and body weight gain. In an in vitro study, NAC treatment to cultured adipocytes repressed lipid accumulation and ROS production [20]. Also, in experimental models of diet induced obesity, NAC supplementation exhibited weight reduction effect [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…FOXOs are implicated in a broad range of cellular functions, and these are cellular properties, critical to the cell biology, including cellular differentiation, apoptosis, cell proliferation, DNA damage, and repair [42,43]. Obesity leads to the progression of insulin resistance and type II diabetes mellitus [44], and studies have reported that insulin signaling pathways regulate adiposity cell differentiation [45]. Therefore, these signaling pathways may be keys to further explore the molecular mechanisms underlying chicken adipose differentiation.…”
Section: Discussionmentioning
confidence: 99%